PELAKSANAAN SUPERVISI AKADEMIK OLEH PENGAWAS DALAM MENINGKATKAN KINERJA GURU IPS PADA SMP NEGERI KABUPATEN GAYO LUES - Masitah Br S, Cut Zahri Harun, Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
ABSTRACT: Academic supervision is an assistance provided to teachers to improve the ability, learning process and their performance. The purpose of this study was to find out academic supervision program, academic supervision implementation, academic supervision techniques and follow up activities of academic supervision implementation at State Junior High Schools of Gayo Lues Regency. This study used qualitative approach and descriptive method. Data were collected through interviews, observation and documentation study. Subjects in this study were school supervisors, principals and teachers. The results showed that (1) The program of supervision that has not been done organized by supervisors in school scheduled like planning, scheduled of activities and programming; (2) The but implementation of academic supervision has been implemented, although has not been scheduled but implementation, assessment, and development remain to be implemented by the supervisor in school; (3) The techniques of academic supervision carried out were: classroom visits, classroom observations, individual counseling and group counseling; and (4) Follow-up activities were carried out by joining teachers who had same problem together, getting coaching from supervisors and fostering kinship attachment among them, in addition, supervisors can determine the development of teachers as well as the success of teaching. From those it will be seen that teachers can improve their performance and for teachers who did not meet the standards should undertake clinical supervision coaching or ongoing guidance for those who have not been optimal in teaching.Keywords: academic supervision, school’s supervisor and teacher performance ABSTRAK: Supervisi akademik merupakan bantuan yang diberikan kepada guru untuk meningkatkan kualitas pembelajaran. Tujuan penelitian ini untuk mengetahui bagaimana program supervisi akademik, pelaksanaan supervisi akademik, teknik-teknik supervisi akademik dan tindak lanjut pelaksanaan supervisi akademik pada SMP Negeri Kabupaten Gayo Lues. Penelitian ini merupakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dan studi dokumentasi. Subjek dalam penelitian ini adalah pengawas sekolah, kepala sekolah, dan guru. Hasil penelitian menunjukkan bahwa (1) Program supervisi akademik oleh pengawas di sekolah belum tersusun baik perencanaan, jadwal kegiatan, dan pelaksanaan program; (2) Pelaksanaan supervisi sudah terlaksana, meskipun belum terjadwal pelaksanaan, penilaian dan pembinaan tetap dilaksanakan oleh pengawas; (3) Teknik-teknik supervisi akademik dilakukan dengan kunjungan kelas, observasi kelas, bimbingan individual, dan bimbingan kelompok; dan (4) Tindak lanjut supervisi akademik dilakukan dengan mengikutsertakan guru yang permasalahan sama, mendapatkan pembinaan dari pengawas, sehingga guru dapat meningkatkan kinerja, bagi guru yang belum memenuhi standar harus dilakukan pembinaan, supervisi klinis atau bimbingan berkelanjutan bagi guru yang belum maksimal dalam mengajar.Kata kunci: supervisi akademik, pengawas sekolah, dan kinerja guru